FIGURATIVE LANGUAGE ON VISUAL IMAGERY OF VOICES OF THE NIGHT BY HENRY WODSWORTH LONGFELLOW - Suyudi, Suyudi (UG Journal, 2021)
Figurative language and imagery play important roles in literary works. This research analyzes the application of Figurative language and visual imagery in poetry. The research problems are: (1) What are visual imagery used in the five selected poem by Henry Wodsworth Longfellow?, (2) What are types of figurative language found on visual imagery of the selected poems? This research aims to analyze visual imagery and types of figurative language on visual imagery in “Prelude, Hymn to the night, a psalm of life, The Reaper and the sunflower, foursteps of angels.” This research show the most dominant types of figurative language. The research method is descript ive qualitative which attempt to describe and interpret the objects in accordance with reality. The data of this research is taken from five selected poems of voices of the night collected volume .The data is then analyzed further by describing the visual imagery and figurative language of the visual imagery. The result of this research shows two things: first, The result of this research shows that the percentage of visual imagery with and without figurative language are 42,7 % and 58,5 %. The second result of this research shows that there are four types of figurative language of visual imagery used in the five selected poems. The result is as follows: simile (5,7%), Metonymy (12,4%),Hyperbole (4,5%) ,Personification (20,3%), The most dominant type figurative language is personification. This research contributes further understanding of the application of figurative language in literary work especially in the field of poetry.